Socio-cultural differentiation of youth in the Republic of Adygeya (historical aspect) - Julia Yurievna Migunova (Вестник Майкопского государственного технологического университета, 2023)
The article reveals the problem of increasing the social differentiation of Russian youth in the soviet and post-soviet periods. The purpose of the research is to analyze sociocultural activities of soviet youth and to identify the role of the Komsomol in their lives. The content analysis of the regional press was used as a method of scientific research. The article provides a qualitative analysis of the causes and significant factors of the evolution of youth associations, which determined their transition from traditional soviet ideology of unity of youth and the KPSU party structures to new organization forms based on the principle of self-sufficiency and multi-variant ideological basis. The results of the research helped to identify problems of inclusion of young people in public life common for the soviet and post-soviet periods, which young people stopped to perceive as a pressing need after the collapse of the Komsomol. The result was the emergence of a large number of informal associations, which gave rise to social differentiation among the youth. Apart from social stratification, exacerbation of conflicts and growth of social tension, the differentiation of social composition of youth takes on negative forms when undesirable effects of mismatch and aggravation of contradictions among young people about inequality are provoked. These phenomena lead to a violation of social integrity, which once again highlights the importance of the investigated topic.